Sistem Informasi Lowongan Kerja di Kota Sampit Berbasis Web - Musfika, Puput Nada; Rusda, Depi (Forum Kerjasama Pendidikan Tinggi, 2020)
The need for information is very much needed in line with the rapid technological advances in modern times such as today, especially the use of computerized systems that propagate in all fields. So, every Human Resource (HR) must always be required to fulfill the expertise, skills and abilities in running a computer hardware or software. In the field of information delivery services to companies or agencies that require labor, such as those in Sampit City, Central Borneo, currently information is conveyed only through several media such as newspapers, magazines, and information obtained by word of mouth. This makes it difficult to find accurate information for job applicants, and for companies it is also difficult to find prospective employees in a time efficient manner because it is still done without an information system. With the development of information technology, it is necessary to provide an Information System to solve problems in delivering job information directly from companies. With this Information System, applicants will also find it easy to receive information, submit job application files, and take written tests online. And the company will get employees in an effective and time-efficient way, starting from the delivery of information, file selection, written tests and passing results from written tests that can be processed directly through this information system.